The Effect of Job Motivation and Job Satisfaction on Employee Performance through Organizational Citizenship Behavior - Hariati Hariati; Mahlia Muis; Yunus Amar (Hasanuddin Journal of Business Strategy, 2021)
This study aims to determine and analyze the effect of work motivation and job satisfaction on employee performance with organizational citizenship behavior (OCB) as an intervening variable at PDAM Wae Manurung in Bone Regency. Data collection was conducted through observation and questionnaires. The data are then analyzed using path analysis and evaluated their validity and reliability, classical assumption tests, and Sobel tests beforehand. The results showed that work motivation had a positive and significant effect on organizational citizenship behavior. Job satisfaction has no effect on organizational citizenship behavior. Work motivation has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Organizational citizenship behavior has a positive effect on employee performance. Work motivation affects employee performance through organizational citizenship behavior. Job satisfaction has no effect on employee performance through organizational citizenship behavior.